Strategies for Driving and Development problem solving ability of kindergarten students school group in Phongprasat sub-district network at Prachuapkirikhan Primary Education Service Area 1 - Noimuang, Saitan; Lenanant, Apichat (Journal of MCU Phetchaburi Review, 2025)
The objectives of this research were to study 1) strategies for driving the development of problem-solving abilities of kindergarten students, 2) strategies for developing problem-solving skills in kindergarten students, 3) Results of the development of problem-solving ability of kindergarten students in the Phongprasat Subdistrict Network School Group, under the Office of the Prachuap Khiri Khan Primary Educational Service Area 1 the target group is 3 teachers from Pongprasat Street Network School and 40 third-grade kindergarten students. The research tools consist of 1) strategic manual for promoting and developing problem-solving skills among kindergarten students with the index of item objective congruence (IOC) between 0.67-1.00 , and 2) an assessment of problem-solving ability of kindergarten students with the index of item objective congruence (IOC) between 0.67-1.00. The statistics used for data analysis included mean, standard deviation, and percentage of progress. The results of this research were as follows : 1. Strategies used to drive the development of problem-solving thinking skills of kindergarten students in the Phongprasat Subdistrict Network School Group, under the Office of the Prachuap Khiri Khan Primary Educational Service Area 1 consisted of 4 strategies : 1) Networking Strategy 2) Participation Strategy 3) Empowerment Strategy and 4) Integration Strategy 2. Strategies used to develop problem-solving skills of kindergarten students in the Pongprasat Subdistrict Network School Group, under the Office of the Prachuap Khiri Khan Primary Educational Service Area 1 was the PPE strategy. The strategy consisted of 3 steps : 1) Present 2) Practice 3) Evaluate and 3. The results of development problem-solving ability of kindergarten students in the Phongprasat Subdistrict Network School Group, under the Office of the Prachuap Khiri Khan Primary Educational Service Area 1 showed the percentage of progress at 34.51